Designing and Developing Apparel Products from Local Woven Fabric of Nan Province, Thailand - Roonreangjai, Rueankhwan (Area Based Development Research Journal, 2024)
Thai Lue Woven Fabric with Natural Color from Ban Don Moon Village, Ban Chao Luang Weaving Community Enterprise Group, and Prapassorn Woven Fabric of Nan are local weaving groups in Nan Province, Thailand. These groups were formed by local people to create job opportunities based on the weaving culture. However, their weaving products have faced limitations in design and response to current consumer demands. This research aims to modernize apparel products made from the cultural capital of woven fabric from each group. The goal is to convey the uniqueness of the local woven fabric and add value to expand the customer base through a collaborative network of members and related individuals. The research process includes: 1) analyzing potential and setting goals, 2) generating ideas for the design and development of local weaving products, 3) designing and developing the products, 4) creating drawings of apparel products from the local woven fabric, 5) producing prototype apparel products, 6) promoting product processing skills, and 7) testing the market for prototype apparel products. All groups collaborated to define ideas for design and development, including color tones and materials. They developed production capabilities, prototyping, and patterning, promoted sewing skills within the network, and mixed materials from network members to create modern apparel products. This effort aimed to build a business community based on interdependence. As a result, Thai Lue Woven Fabric with Natural Color from Ban Don Moon Village incorporated dyeing and weaving techniques obtained from mixed processed fibers. The research produced 8 designs of apparel products from local woven fabric, which could be distributed at higher prices, resulting in a 45% - 100% price increase. This added value to the woven fabric by an average of 63.29%. Consumers expressed high satisfaction with the products, which could help preserve cultural heritage for future generations.